Modern pharmacotherapy of chronic hepatitis C in patients who failed to achieve sustained virologic response - Kireyev, I; Zhabotynska, N (Annals of Mechnikov’s Institute, 2020)
Introduction. According to WHO experts, about 150 million people suffer from chronic viral hepatitis C (CHC), and 350,000 die annually as a result of liver damage by the hepatitis C virus (HCV). Ukraine is one of the countries with medium prevalence of CHC – about 3% of citizens are infected. CHC has become a treatable disease with the use of antiviral drugs (> 95%). To date, for the pharmacotherapy of CHC, a combination of pegylated interferon (PEG-IFN) with ribavirin and direct-acting antivirals (DAAs) are used. Pharmacotherapy of СHC using a combination of PEG-IFN and ribavirin has a relatively high efficiency, but it depends on the genotype of the HCV. Therefore, the use of DAAs is a priority in pharmacotherapy of chronic hepatitis C. Patients who failed to achieve sustained virologic response (SVR) are given a second course of treatment (retreatment). The decision on this is based on the following main positions: the nature of the previous response, the type of previous therapy and the potential for a new type of treatment, the severity of liver damage, the genotype of the virus and the presence of other prognostic factors and tolerance to previous therapy. Material & methods. The article analyzes the recommendations of the American Society of Infectious Diseases (IDSA) and the American Association for the Study of Liver Diseases (AASLD), in collaboration with the US International Anti-Virus Society (IAS-USA), as well as the WHO recommendation for repeated pharmacotherapy of CHC in patients who failed to achieve SVR. Results & discussion. To date, for re-treatment of CHC in patients receiving treatment without achieving a SVR, the different re-treatment regimens are recommended depending on the genotype of the HCV. An important problem during pharmacotherapy of patients with CHC is resistance to antiviral therapy. The amino acid polymorphism of NS3, NS5A and NS5B viral proteins in different HCV genotypes and subtypes, as well as the same strains of genotypes and subtypes that reduce DAAs efficacy, is referred to as resistance-related variants (RRV). However, antiviral therapy fails only when RRV is combined with other factors and features of the patient’s body, decreased sensitivity to antiviral therapy, or insufficient duration of therapy. As seen in the recommendations for recurrent CHC pharmacotherapy, possible resistance to the protease inhibitor NS5A and to the NS3 protease inhibitors was considered. Conclusion. The results obtained from published sources indicate that current strategies for recurrent pharmacotherapy of CHC patients in most cases of unsuccessful pre-treatment allow the achievement of SVR using DAAs during re-treatment, including those regimens that have efficacy in resistance-associated variants.